2012
DOI: 10.1016/j.neuroimage.2012.08.049
|View full text |Cite
|
Sign up to set email alerts
|

A 10-year longitudinal fMRI study of narrative comprehension in children and adolescents

Abstract: Comprehension of spoken narratives requires coordination of multiple language skills. As such, for normal children narrative skills develop well into the school years and, during this period, are particularly vulnerable in the face of brain injury or developmental disorder. For these reasons, we sought to determine the developmental trajectory of narrative processing using longitudinal fMRI scanning. 30 healthy children between the ages of 5 and 18 enrolled at ages 5, 6, or 7, were examined annually for up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
52
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 75 publications
10
52
0
1
Order By: Relevance
“…Thus, it is especially provocative that there are reliable gender differences in autobiographical narratives (see , for a review), such that females tell more detailed, more elaborated, more emotionally expressive, and more relationally oriented personal narratives than do males. Equally importantly, we do not see gender differences in other forms of narratives, such as fictional stories (Szaflarski et al, 2012;Weiss, Kemmler, Deisenhammer, Fleischhacker, & Delazer, 2003) or narrative descriptions of witnessed events that are not personally significant (Jack, Leov, & Zajac, 2014). These patterns suggest that the observed gender differences are not related to narrative skills per se, but are rooted in gender differences in narrating important aspects of identity.…”
Section: Introductionmentioning
confidence: 60%
“…Thus, it is especially provocative that there are reliable gender differences in autobiographical narratives (see , for a review), such that females tell more detailed, more elaborated, more emotionally expressive, and more relationally oriented personal narratives than do males. Equally importantly, we do not see gender differences in other forms of narratives, such as fictional stories (Szaflarski et al, 2012;Weiss, Kemmler, Deisenhammer, Fleischhacker, & Delazer, 2003) or narrative descriptions of witnessed events that are not personally significant (Jack, Leov, & Zajac, 2014). These patterns suggest that the observed gender differences are not related to narrative skills per se, but are rooted in gender differences in narrating important aspects of identity.…”
Section: Introductionmentioning
confidence: 60%
“…However, like the Veroude et al study, we also focused on adult learners. A study of adults, as opposed to children, allows for a view of activation changes associated with learning that is independent of the changes associated with maturation (e.g., Plante, Holland, & Schmithorst, 2006; Schmithorst, Holland, & Plante, 2007; Szaflarski, Altaye, Rajagopal, Eaton, Meng, Plante, & Holland, 2012; Szaflarski, Schmithorst, Altaye, Byars, Rett, Plante, & Holland, 2006). In children who are acquiring language, these two constructs can be difficult to dissociate.…”
Section: Introductionmentioning
confidence: 99%
“…Further, studies have shown that acute and subacute language recovery may be dependent on different neural substrates, with early contributions from the right hemisphere and later language abilities dependent on the left hemispheric peristroke regions (Saur et al, 2006). This issue – timing of the insult – is very important as age-dependent changes in language localization and lateralization have been observed in various cross-sectional and longitudinal studies of healthy children and adults (Springer et al, 1999; Szaflarski et al, 2002, 2006a, 2012a, 2012b). Thus, an acute lesion may have a different effect on function recovery across ages.…”
Section: Introductionmentioning
confidence: 99%